Analysis of Cultural Tourism Development, Accessibility, and Community Involvement on the Attractiveness of Tourism Destinations in Bali - Ni Desak Made Santi Diwyarthi; Rahmi Setiawati; I Wayan Adi Pratama; Darmawan Listya Cahya; Muchlis Daroini (West Science Interdisciplinary Studies, 2024)
This study investigates the influence of cultural tourism development, accessibility, and community involvement on the attractiveness of tourism destinations in Bali. Employing a quantitative approach, data were collected from 210 respondents using a structured questionnaire with a Likert scale ranging from 1 to 5. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results reveal that accessibility has the strongest positive effect on attractiveness, followed by community involvement and cultural tourism development. These findings underscore the importance of integrating infrastructure development, active community participation, and cultural preservation to enhance Bali's appeal as a global tourist destination. The study provides actionable insights for policymakers and tourism stakeholders to promote sustainable and inclusive tourism development.